Determinants of Short-Term Financing Among Islamic Savings Co-Operatives in Thailand - Noipom, Tawat (2003)
This research investigates the relationship between profitability, liquidity, and management preference and the use short-term modes of financing among Islamic savings co-operatives in Thailand. The results of this research will shed some light on whether profitability, liquidity and management preference are determinants of short-term financing in the co-operatives. Both descriptive statistics and regression analysis are used in this study. Descriptive analysis is used to explain the relationship between short-term financing and management preference. Regression analysis is applied to obtain the relation of short-term financing to profitability and liquidity. Data used in descriptive analysis is obtained via a questionnaire. Data on short-term financing, profitability, liquidity and other two contributing factors i.e. solvency and activity is obtained from secondary data mainly income statements, balance sheets and statements of cash flow. The raw data is transformed to financial ratios to represent profitability, liquidity, solvency and activity management. Short-term financing is calculated from the change of short-term financing over the period. The results of the regression analysis show that the profitability, liquidity, and activity management of the co-operatives are determinants of short-term financing in the co-operatives. The results confirm opinions being expressed by most executive board members and staff of the co-operatives who agreed, during the survey session, that profitability and liquidity are the two main concerns for the co-operatives to rely heavily on short-term modes of financing. The management of the co-operatives agree somewhat that they prefer short-term financing.